Two new species of Machaerotidae from the Democratic Republic of the Congo, with some additional records of the family (Hemiptera: Cercopoidea) - Haas, Matthé Cornelis De; Mertens, Jan E. J. (Zootaxa, 2024)
Machaerotidae is a small family with a paleotropical distribution. Eight species are known from Africa. Labramachaerota luilaka sp. n. and Labramachaerota salonga sp. n. are described from Salonga National Park and along the Luilaka river in the buffer zone between the western and eastern sides of this National Park, situated in the Congo Basin in the Democratic Republic of the Congo. Enderleinia bispina Schmidt, 1907 is also recorded from the buffer zone of the Salonga National Park and several other locations, which are the first specified records of this species from the Democratic Republic of the Congo. Neuromachaerota discigutta Maa, 1963 is here recorded for the first time from the Democratic Republic of the Congo.